Online Information on Probiotics: Does It Match Scientific Evidence? - Neunez, Marie; Goldman, Michel; Ghezzi, Pietro (Frontiers in Medicine, 2020)
Probiotics are over-the-counter products marketed for enhancing human health. Online information has been key in promoting probiotics worldwide. However, only few rigorous clinical studies have met the stringent criteria required to establish the efficacy and safety of probiotics. The present study was undertaken to assess the information quality of webpages referring to probiotics and to compare the recommendations available online with the information collected from trusted scientific sources. We evaluated 150 webpages returned by Google searching “probiotics” in terms of typology of website, health information quality based on the JAMA score and the HONcode certification, as well as completeness of the information based on the presence of 4 criteria: (1) links to scientific references supporting health claims, (2) cautionary notes about level of evidence for alleged benefits, (3) safety considerations and (4) regulatory status. We then enumerated the health claims mentioned online and the corresponding clinical trials and reviews registered in the Cochrane library. Finally, the conclusions of Cochrane reviews were used to assess the level of scientific evidence of the information available through Google search. The results of this analysis led us to conclude that: (1) the most frequent typologies of webpages returned by Google are commercial and news, (2) commercial websites provide the least reliable information and (3) significant numbers of claimed benefits of probiotics are not supported by scientific evidence. This study highlights important biases in the probiotics information available online, underlining the need to develop reliable communication channels independent from commercial interests.